A "dark side" to French parliamentary diplomacy? Evidence from the Syrian and Ukrainian conflicts. Issue 2 (15th March 2021) - Stavridis, Stelios
ABSTRACT: International democratic theory suggests that democratic states should act according to certain principles, values and rules. Even if such an approach often depends on circumstances, it should remain their objective, including in international conflicts. Recent literature on parliamentary diplomacy has also illustrated this situation with empirical examples, including in the case of French parliamentary diplomacy. Yet, in the Syrian and Ukrainian conflicts, existing literature shows numerous examples which contravene these accepted standards. In fact, they support anti–democratic regimes instead. In addition, many an academic writing on the subject appears to celebrate such a behaviour. This article will therefore unpack this French puzzle. Its aim is not to criticize the concept or practice of parliamentary diplomacy. Its objective is to highlight why there might exist a "dark side" to French parliamentary diplomacy. A cause for serious concern that has been largely ignored by academics and practitioners to date.